RESILIENCE IN FOREIGN LANGUAGE LEARNING: A STUDY ON PRE-SERVICE TEACHERS' LANGUAGE LEARNING EXPERIENCES - Hande Serdar Tuluce (Informascope, 2018)
Investigating pre-service teachers' language learning experiences is essential as they have an impact on their learning during their departmental studies and their future teaching practices. Given the fact that there is a growing call for the development of resilience in teacher education programs, this qualitative study aims at exploring what resources pre-service English language teachers have relied on to overcome challenges and obstacles to learning English as a foreign language. To achieve this aim, data were obtained from 23 pre-service teachers enrolled in English Language Teaching program at a university in Istanbul, Turkey in the form of a reflective writing activity. To triangulate data, a focus group interview was carried out with five of the participating pre-service teachers. Data were analyzed using the thematic analysis approach (Braun & Clarke, 2006). Findings revealed that pre-service teachers dealt with a variety of obstacles in their English language learning histories such as ineffective methodologies used by teachers, anxiety caused by examinations, obstacles in language skills especially speaking, and language barriers while staying in English-speaking countries. The pre-service teachers mentioned that they demonstrated agency in the process of overcoming these obstacles and their resilience included both personal protective factors and social/environmental protective factors. Keywords: resilience, positive psychology, teacher education, foreign language learning